Pengaruh Lama Pengeringan Terhadap Sifat Kimia dan Fisik Daun Salam (Syzgium polyanthum) - Anggraini, Ines Marisya Dwi; Mulachela, Fathiyah; Zainuri, Zainuri; Handito, Dody (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2024)
Bay leaves (Syzygium polyanthum) is a spice plant from Indonesia which can be used for various medical and non-medical purposes. Bay leaves contain various bioactive compounds. the shelf life of bay leaves can be extend by drying method. The drying process can damage the nutritional content of post-harvest products, especially bioactive components. The aim of this research was to analyze the effect of drying time using the oven method on the chemical and physical properties of bay leaves. Drying was carried out using an oven equipped with a blower with a temperature for all treatments of 50 oC and drying time of 50 minutes, 70 minutes, 90 minutes, 110 minutes, 130 minutes and 150 minutes. The parameters observed in this research were antioxidant activity, water content, ash content, color and yield of dried bay leaves. The observation data was analyzed for diversity (Analysis of Variance) with a significance level of 5% using Costat software. If there is a real difference between treatments, then it is tested further using the Difference in Tendency test or Orthogonal Polynomial Method (MOP) at the 5% level. The length of drying time had a significantly different effect on antioxidant activity, water content and yield, but was not significantly different on ash content and color. The longer the drying time, the lower the antioxidant activity, water content and yield of bay leaves.